2018
DOI: 10.5812/compreped.69006
|View full text |Cite
|
Sign up to set email alerts
|

Is Renal Bladder Ultrasound Necessary in Monosymptomatic Primary Nocturnal Enuresis? A Case Control Study

Abstract: Background: Primary nocturnal enuresis is the most common type of enuresis and has profound detrimental effects on quality-oflife and sleep patterns, and increased morbidity. The purpose of this study was to determine the frequency of urinary tract abnormalities found in ultrasound of children with monosymptomatic primary nocturnal enuresis (MPNE) and to compare with ultrasound findings of children without MPNE to determine whether performing ultrasound in these children is necessary. Methods: One hundred and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…In agreement with our results, Siroosbakht and Rezakhaniha 10 concluded that urinary abnormalities discovered by ultrasonography in PMNE are more than the control group and these findings are not clinically significant and do not require any other diagnostic tests. It may only be of concern to parents and cause unnecessary diagnostic procedures by the physician.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our results, Siroosbakht and Rezakhaniha 10 concluded that urinary abnormalities discovered by ultrasonography in PMNE are more than the control group and these findings are not clinically significant and do not require any other diagnostic tests. It may only be of concern to parents and cause unnecessary diagnostic procedures by the physician.…”
Section: Discussionsupporting
confidence: 93%
“…Because prenatal ultrasonography can detect many abnormalities, this report recommends using it in any baby with intrauterine growth retardation (IUGR). Prenatal detection of such anomalies can help to avoid delays in diagnosis and multidisciplinary care for these infants after birth (11). Furthermore, overuse of this modality in normal pregnancy may cause parents to be concerned and primary care providers to use unnecessary diagnostic modalities.…”
Section: Discussionmentioning
confidence: 99%
“…As a general term, bladder dysfunctions that lead to voiding dysfunction describe abnormalities in filling and emptying the bladder (1). This is the most common urological condition constituting more than 40% of pediatric urology clinic visits, and is classified as diurnal and nocturnal enuresis (2).…”
Section: Introductionmentioning
confidence: 99%
“…Factors that may induce urination dysfunction include the difference in developmental aspects, organic disorders, delayed bladder maturation, psychological distress, genetic factors, low bladder volume, deep sleep, and low level of vasopressin (4). Also, medical problems that may contribute to bedwetting include diabetes, UTIs, constipation, pinworms, kidney failure, seizures, and sleep problems (1,8).…”
Section: Introductionmentioning
confidence: 99%